Polish non-treasury bond market – key statistics, legal evolutions and development challenges - Martysz, Czesław Bartłomiej (Journal of Finance and Financial Law, 2025)
The purpose of the article. The article aims to present key statistics of the Polish market for non-treasury debt securities, to show the essence of the tightening of legal regulations and their impact on the development of the market, as well as to identify market development problems and de lege ferenda proposals to improve its attractiveness to investors and issuers in the long term.Methodology. The article follows the author's previous publication in 2020 and is unique in that it shows the market for non-treasury debt securities in a cross-sectional manner based on an analysis of legal acts and press publications, the latest and partly non-public statistics of the KDPW, and the author's market practice.Results of the research. The nominal value of the Polish non-treasury bond market is PLN 454.2 billion, but excluding the quasi-treasury securities of BGK, PFR and EIB, it is PLN 157.6 billion, of which only 49.4% of the securities are listed on the Catalyst market, which is celebrating its 15th anniversary this year. Between 2017 and 2024, the bond law was significantly tightened to protect retail investors, whose real share of the primary market is small, from misselling. The new law raises many questions and complicates the issuance process, raising questions about whether it will ultimately help or hurt market development. Many retail investors will not take advantage of improved market transparency and access to new information due to lack of economic knowledge. In addition to the new regulations, challenges to the non-treasury debt securities market also remain, including lack of financial education, reluctance of new issuers to enter the bond market, lack of ratings and insufficient analytical coverage of issuers, lack of standardization of documentation, and lack of secondary market animation and liquidity.